Wall Street analysts as investor relations officers - Hope, Ole-Kristian; Huang, Zhongwei; Moldovan, Rucsandra (Journal of Corporate Finance, 2021)
This paper examines the practice of hiring financial analysts as investor relations officers (IRO). We posit that analysts-turned-IROs (AIROs) have a competitive advantage in communicating with investors, thereby lowering the effort expended by the investment community to process corporate disclosures. Using a unique manually-collected dataset on the employment history of IROs compiled from LinkedIn, Capital IQ, RelationshipScience.com, and appointment press releases, we show that disclosure readability in 8-K and 10-K filings improves and that companies are more likely to host analyst/investor days after hiring former analysts as IROs. Most importantly, we find increases in analyst following, institutional investors, and stock liquidity after hiring a former analyst as IRO. We conclude that both a disclosure and a network channel are at play in the relation between AIROs and increased interest from the investment community. Overall, our findings suggest that firms benefit from hiring Wall Street analysts as IROs.